DIALEKTIKA PERLINDUNGAN KEPENTINGAN NASIONAL BERDASARKAN KONSTITUSI EKONOMI DENGAN BASIC PRINCIPLE DALAM BILATERAL INVESTMENT TREATIES - Widhayani Dian Pawestri (Yuridika, 2016)
National interests is a fundamental thing that is often discussed, but does not have the exact concept and parameters. Especially in investment, national interests increasingly reduced by the emergence of some problems in Bilateral Investment Treaties (BIT), and certainly, the most disadvantaged entity is the State. This paper examines the dialectic between national interests with the basic principle, as one of the principles in the WTO-TRIMs that should be applied by all the States that have ratified that convention, including Indonesia. If there is a conflict between the national interest and the basic principle, especially in BIT, then the state must remain in favor of its national interests. The underlying basis of the argument is that the State has sovereignty whose power must be maintained. This is in line with the 'calvo doctrine' and the basic essence that the state (in this case the host state) has sovereignty over all natural resources-permanent sovereignty over natural resources-such as environmental protection, health and protection of human rights.